Comparative and functional genomics of closteroviruses - Dolja, V.V.; Kreuze, Jan F.; Valkonen, J.P.T. (Elsevier, 2006)
The largest extant RNA genomes are found in two diverse families of positive-strand RNA viruses, the animal Coronaviridae and the plant Closteroviridae. Comparative analysis of the viruses from the latter family reveals three levels of gene conservation. The most conserved gene module defines RNA replication and is shared with plant and animal viruses in the alphavirus-like superfamily. A module of five genes that function in particle assembly and transport is a hallmark of the family Closteroviridae and was likely present in the ancestor of all three closterovirus genera. This module includes a homologue of Hsp70 molecular chaperones and three diverged copies of the capsid protein gene. The remaining genes show dramatic variation in their numbers, functions, and origins among closteroviruses within and between the genera. Proteins encoded by these genes include suppressors of RNA silencing, RNAse III, papain-like proteases, the AlkB domain implicated in RNA repair, Zn-ribbon-containing protein, and a variety of proteins with no detectable homologues in the current databases. The evolutionary processes that have shaped the complex and fluid genomes of the large RNA viruses might be similar to those that have been involved in evolution of genomic complexity in other divisions of life.